Delayed Endophthalmitis Due To Severe Corneal Ulcer - Pramadhari, Carnetta Andira; Anggraini, Irastri (Jurnal Ners, 2025)
Globally, an estimated 1.2–2.0 million cases of infectious keratitis occur annually, with delayed treatment leading to endophthalmitis in 6–12% of cases. Endophthalmitis is an ophthalmological emergency condition that occurs due to severe intraocular inflammation caused by infection. This condition requires immediate intervention to prevent permanent blindness. In Indonesia, corneal ulcers rank as the second-leading cause of blindness nationally, with 30–40% of cases linked to agricultural injuries. Delayed corneal ulcer management can lead to complications like endophthalmitis. This study highlights the importance of understanding and early intervention regarding endophthalmitis associated with ophthalmological emergencies that can result in blindness. We reported a 66-year-old man with a history of eye contact with rice had gone to the community health center, but it could not be treated. Came to the Wongsonegoro Hospital Ophthalmology Clinic with complaints of constant pain in his left eye for the last month. Visual acuity OD 6/60 and OS 1/~ LP. Ophthalmological examinations of the left eye revealed mixed injection, hypopyon in COA in the anterior and posterior segment involvement with elevated digital IOP. Infiltrative ulcer lesions were observed at 1–6 o'clock in the temporal region. Funduscopic examination was not performed. He received analgesics, antibiotics, vitamin C, and artificial tears and was planned for evisceration.